SECONDARY MELT INCLUSIONS IN OLIVINE FROM UNALTERED KIMBERLITES OF THE UDACHNAYA-EAST PIPE, YAKUTIA - Golovin A.V.; Sharygin V.V.; Pokhilenko N.P.; Mal'kovets V.G.; Sobolev N.V.; Kolesov B.A. (My University, 2003)
In the central part of the Udachnaya-East kimberlite pipe situated in the Daldyn–Alakit district of the Yakutian kimberlite province, unique (in the high degree of its preservation) kimberlitic rock with abundant olivine, which did not undergo serpentinization, was found at a depth of 350–650 m. This kimberlite can be regarded as a reference primary rock that retained all features of the deep-seated melt [1].